High-contrast observations of brown dwarf companion HR 2562 B with the vector Apodizing Phase Plate coronagraph. Issue 3 (5th July 2021) - Sutlieff, Ben J; Bohn, Alexander J; Birkby, Jayne L; Kenworthy, Matthew A; Morzinski, Katie M; Doelman, David S; Males, Jared R; Snik, Frans; Close, Laird M; Hinz, Philip M; Charbonneau, David
ABSTRACT: The vector Apodizing Phase Plate (vAPP) is a class of pupil plane coronagraph that enables high-contrast imaging by modifying the Point Spread Function (PSF) to create a dark hole of deep flux suppression adjacent to the PSF core. Here, we recover the known brown dwarf HR 2562 B using a vAPP coronagraph, in conjunction with the Magellan Adaptive Optics (MagAO) system, at a signal-to-noise of S/N = 3.04 in the lesser studied L -band regime. The data contained a mix of field and pupil-stabilized observations, hence we explored three different processing techniques to extract the companion, including Flipped Differential Imaging (FDI), a newly devised Principal Component Analysis (PCA)-based method for vAPP data. Despite the partial field-stabilization, the companion is recovered sufficiently to measure a 3.94 $μ m$ narrow-band contrast of (3.05 ± 1.00) × 10 −4 ($Δ \, {\rm m}_{3.94 μ {\rm m}}$ = 8.79 ± 0.36 mag). Combined with archival GPI and SPHERE observations, our atmospheric modelling indicates a spectral type at the L/T transition with mass M = 29 ± 15 MJup, consistent with literature results. However, effective temperature and surface gravity vary significantly depending on the wavebands considered (1200 ≤ T eff (K) ≤ 1700 and 4.0 ≤ log(g)(dex) ≤ 5.0), reflecting the challenges of modelling objects at the L/T transition. Observations between 2.4 and 3.2 $μ m$ will be more effective in distinguishing cooler brown dwarfs due to the onset of absorption bands in this region. We explain that instrumental scattered light and wind-driven halo can be detrimental to FDI+PCA and thus must be sufficiently mitigated to use this processing technique. We thus demonstrate the potential of vAPP coronagraphs in the characterization of high-contrast substellar companions, even in sub-optimal conditions, and provide new complementary photometry of HR 2562 B.